What future for Chinese labour and transnational solidarity? - Bieler, Andreas; Lee, Chun-Yi (Taylor and Francis, 2016)
In this conclusion we argue that class struggle is central to the future of Chinese workers and the improvement of their situation. Technological upgrading in itself will not automatically result in better working conditions. Moreover, we point out that Chinese workers have a number of old and new sources of power to draw on. What is, however, most problematic in this respect is the role of the ACFTU, operating as an official mediator rather than an independent trade union, and the resulting lack of associational power. Hence, informal labour NGOs have an important role to play in supporting social justice for China’s workers.